Empowerment of Pendawa Farmer Group to Improve Quality of Cocoa Product - Harahap, Edy Syahputra; Akasah, Wida; Alfi, Rahmatika; Nursa’adah (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The Pendawa farmer group located in Candirejo Village, Sibiru-biru, Deli Serdang, North Sumatra has processed cocoa beans into milk chocolate bars. The aims this activity is to find and increase the melting point temperature of milk chocolate bar products that have been produced by farmers. The low melting point causes the chocolate produced by the Pendawa farmer group to not last long and easily melts at room temperature in a short time. Some of the innovations the team provided were the addition of vegetable oil (coconut oil) and the addition of a tempering process before the chocolate was molded/frozen. The tempering process aims to change the shape of the crystals in chocolate. Based on observations, chocolate with coconut oil added has a good aroma and a shinier appearance compared to chocolate without coconut oil added. In addition, milk chocolate bar products with the addition of a tempering process have a higher melting point temperature than non-tempered products. Products with the tempering process also show a denser form than non-tempered chocolate bars.